Diffuse alveolar haemorrhage in children: an international multicentre study. Issue 2 (24th April 2023) - Ring, Astrid Madsen; Schwerk, Nicolaus; Kiper, Nural; Aslan, Ayse Tana; Aurora, Paul; Ayats, Roser; Azevedo, Ines; Bandeira, Teresa; Carlens, Julia; Castillo-Corullon, Silvia; Cobanoglu, Nazan; Elnazir, Basil; et al.
Background: Paediatric diffuse alveolar haemorrhage (DAH) is a rare heterogeneous condition with limited knowledge on clinical presentation, treatment and outcome. Methods: A retrospective, descriptive multicentre follow-up study initiated from the European network for translational research in children's and adult interstitial lung disease (Cost Action CA16125) and chILD-EU CRC (the European Research Collaboration for Children's Interstitial Lung Disease). Inclusion criteria were DAH of any cause diagnosed before the age of 18 years. Results: Data of 124 patients from 26 centres (15 counties) were submitted, of whom 117 patients fulfilled the inclusion criteria. Diagnoses were idiopathic pulmonary haemosiderosis (n=35), DAH associated with autoimmune features (n=20), systemic and collagen disorders (n=18), immuno-allergic conditions (n=10), other childhood interstitial lung diseases (chILD) (n=5), autoinflammatory diseases (n=3), DAH secondary to other conditions (n=21) and nonspecified DAH (n=5). Median (IQR) age at onset was 5 (2.0–12.9) years. Most frequent clinical presentations were anaemia (87%), haemoptysis (42%), dyspnoea (35%) and cough (32%). Respiratory symptoms were absent in 23%. The most frequent medical treatment was systemic corticosteroids (93%), hydroxychloroquine (35%) and azathioprine (27%). Overall mortality was 13%. Long-term data demonstrated persistent abnormal radiology and a limited improvement in lung function. Conclusions: Paediatric DAH is highly heterogeneous regarding underlying causes and clinical presentation. The high mortality rate and number of patients with ongoing treatment years after onset of disease underline that DAH is a severe and often chronic condition. This large international study paves the way for further prospective clinical trials that will in the long term allow evidence-based treatment and follow-up recommendations to be determined. Diffuse alveolar haemorrhage (DAH) in children is a rare condition. DAH is heterogeneous in its underlying cause, presentation and outcome, with high overall mortality. There is a broad variation in diagnostic workup and medical treatment across Europe. https://bit.ly/40KGoUh